Controllable Li3PS4–Li4SnS4 solid electrolytes with affordable conductor and high conductivity for solid‐state battery. Issue 5 (8th January 2022) - Dong, Pingping; Jiao, Qing; Zhang, Zengcheng; Jiang, Miao; Lin, Changgui; Zhang, Xianghua; Ma, Hongli; Ma, Baochen; Dai, Shixun; Xu, Tiefeng
Abstract: High ionic conductivity, low grain boundary impedance, and stable electrochemical property have become the focus for all‐solid‐state lithium–sulfur batteries (ASSLSB). One of the approaches is to promote the rapid diffusion of lithium ions by regulating the chemical bond interactions within the framework. The structure control of P 5+ substitution for Sn 4+ on lithium‐ion transport was explored for a series of Li3 PS4 –Li4 SnS4 glass–ceramic electrolytes. Results showed that the grain boundary impedance of the glass electrolyte was reduced after heat treatments. The formation of LiSnPS microcrystals, a good superionic conductor, was detected by X‐ray diffraction tests. Electrochemical experiments obtained the highest conductivity of 29.5 S cm −1 at 100°C and stable electrochemical window from –0.1 to 5 V at 25°C. In addition, the cell battery was assembled with prepared electrolyte, which is promoted as a candidate solid electrolyte material with improved performance for ASSLSB.